Integrated molecular analysis of Tamoxifen-resistant invasive lobular breast cancer cells identifies MAPK and GRM/mGluR signaling as therapeutic vulnerabilities. (15th August 2018) - Stires, Hillary; Heckler, Mary M.; Fu, Xiaoyong; Li, Zhao; Grasso, Catherine S.; Quist, Michael J.; Lewis, Joseph A.; Klimach, Uwe; Zwart, Alan; Mahajan, Akanksha; Győrffy, Balázs; Cavalli, Luciane R.; et al.
Abstract: Invasive lobular breast cancer (ILC) is an understudied malignancy with distinct clinical, pathological, and molecular features that distinguish it from the more common invasive ductal carcinoma (IDC). Mounting evidence suggests that estrogen receptor-alpha positive (ER+) ILC has a poor response to Tamoxifen (TAM), but the mechanistic drivers of this are undefined. In the current work, we comprehensively characterize the SUM44/LCCTam ILC cell model system through integrated analysis of gene expression, copy number, and mutation, with the goal of identifying actionable alterations relevant to clinical ILC that can be co-targeted along with ER to improve treatment outcomes. We show that TAM has several distinct effects on the transcriptome of LCCTam cells, that this resistant cell model has acquired copy number alterations and mutations that impinge on MAPK and metabotropic glutamate receptor (GRM/mGluR) signaling networks, and that pharmacological inhibition of either improves or restores the growth-inhibitory actions of endocrine therapy. Highlights: ILC is an understudied breast cancer subtype with a relatively poor response to TAM. In TAM-resistant ILC cells, TAM treatment is associated with activation of PIK3CA, AHR, and androgen signaling. TAM-resistant ILC cells show MAPK1 amplification and hyperactivation, FOXA1 gain, and CEBPD loss. TAM-resistant ILC cells are characterized by mutation of NF1 and multiple GRMs/mGluRs. Inhibition of MEK or glutamate release using Riluzole improves and restores endocrine therapy response in ILC cells.